Status Resistensi Nyamuk Aedes aegypti dari Wilayah Kerja Puskesmas Salido terhadap Malathion 5% dan Alfa-sipermethrin 0,025% - Nesa Pratiwi; Hasmiwati Hasmiwati; Hendriati Hendriati (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: Insecticides resistance status in Aedes aegypti population is one of the factors that influence the successful control efforts of dengue vector. Objectives:To determine the resistance status of Aedes aegypti from Salido Health Center towards malathion 5% and alpha-cypermethrine 0,025%. Methods: This was a descriptive study and collected during December 2019 – June 2020. Those samples were then observed with larval survey and from the ovitrap placed in 100 houses and then maintained in laboratory of parasitology, faculty of medicine Andalas University. To determine the resistance status of Aedes aegyptiusing the bioassay method with the susceptibility test by referring to the guidance of the Ministry of Health based on the 2016 WHO standard using impregnated paper malathion 5% and alpha-sipermethrin 0.025%. Observations were made by recording the number of mosquito deaths in the 15, 30, 45, 60 and 1440 minutes. The percentage of mosquito deaths is calculated after 24 hours of maintenance it is categorized as resistant if the mortality rate is less than 90%, supected to be resistant if the mortality is between 90-97%, and categorized as vunerable if the mortality rate is between 98-100%.Result: The mortality rate of Aedes aegypti for 24 hours by malathion 5% was 95%, the LT50 and the LT90 were 624 minutes and 1.247 minutes respectively. The percentage of mosquito deaths by alpha-sipermetrin 0,025% after 24 hours was 96,25% the LT50 and the LT90 were 526 minutes and 1.163 minutes respectively.Conclusion: that the resistance status of Aedes aegypti from Salido Health Center is resistant towards malathion 5% and alpha-cypermethrine 0,025%.